THE IMPACT OF TAXES AND LEVIES ON MINAHASA'S REGIONAL ORIGINAL INCOME - Billy Boy Rilmonth Manueke; Iren Meiske Pesik; Riski Afrisandi Samsi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Locally-Owned Revenue (PAD) is a crucial source of regional development financing, therefore, it is necessary to analyze the factors influencing it. This study aims to analyze the influence of Regional Taxes, Regional Levies, and Other Legitimate Locally-Owned Revenue on the PAD of Minahasa Regency. This study uses secondary time series data for the period 2018-2022 obtained from the Statistics Indonesia (BPS) of Minahasa Regency. The analysis method used was multiple linear regression with SPSS 26, supplemented by t-tests and f-tests to determine partial and simultaneous effects. The results show that Regional Taxes and Other Legitimate Locally-Owned Revenue have a positive and significant effect on PAD, while Regional Levies have a positive but insignificant effect. Simultaneously, all three variables significantly influence PAD with a coefficient of determination of 99.8%, thus explaining the majority of the variation in PAD.